Dry matter intake in a silvopastoral system of T. diversifolia in high tropics - Estefania Mejia Diaz; Liliana Mahecha Ledesma; Joaquín Angulo Arizala (Agronomía Mesoamericana, 2017)
The aim of this study was to estimate the intake of dry matter forage (CMSf) by grazing holstein cows. The research was conducted in northern Antioquia highlands; a silvopastoral system with Tithonia diversifolia and Cenchrsus clandestinum (SSP) and a monoculture C. clandestinum were used. Were estimated the CMSf by different methodologies and kikuyu:wild sunflower consumption relation, also the interchangeability of two methodologies was determined. There were two conducted trials, in the first trail SSP was used without browsing of wild sun ower and monoculture; in the second trial the same system was applied, with the difference that for the SSP animals browsed the shrubby by themselves. Twelve random infant holstein cows were used in the two systems. CMSf was estimated by indicators (I), agronomic (A) and grazing behavior (C) methods, method I was the reference. In trial I more CMSf was observed in the SSP, with an average of 14.7 kg/day (p<0.05); trial II showed no difference in the CMSf, with an average of 13.3 kg/day (p>0.005). The kikuyu:wild sunflower consumption relation was 95:5. The correlation coefficient of concordance between the methods I and C near to 0 shown that they are not interchangeable. The results suggest that the SSP evaluated supplied sufficient forage to ensure optimal CMSf.